Estimating the Growing Degree Days in the Northwest of Iran based on Climate Change Models - Hasan Zolfaghari; Jafar Masoompourv Samakosh; Shabnam Chahvari (تحقیقات کاربردی علوم جغرافیایی)
The purpose of this study is predicting climate changes and investigating the effect of probable climate change on the growing degree-days in the northwest of Iran. For this purpose the climatic data of seven synoptic stations during a 25 years period (1985-2009) was collected including Oroomieh, Tabriz, Zanjan, Sanandaj, Ghazvin, Kermanshah, and Hamedan were used as the base period and thus temperature variations periods (2030-2011 and 2065-2046) through HadCM3 model was simulated. For the little power of temporal and spatial distinction of this model, its outputs were downscaled using LARS-WG software and presented under Emission Scenarios including A1B (moderate scenario), A2 (maximum or pessimistic scenario), and B1 (minimum or optimistic scenario). Calibration, verification and Performance Model with the rate of the adaption of observed data and the simulated measures through statistics , RMSE and MAE were analyzed. Finally, using the simulated temperature growing degree-day was calculated and compared under 4 Base temperature including 0°,5°,10°, and 15° centigrade in the basic span (1985-2009) and future span (2011-2030 and 2046-2065). The results of simulation show that temperature change in north-west areas under all three A1B, A2, and B1 scenario are increasing in the future, but the differences among these three scenarios in each period is inconsiderable. In total the most temperature increasing was detected as 0/7 centigrade in A2 scenario for 2011-2030 period and 2/3 centigrade under A1B scenario for 2046-2065 period. Generally with the temperature increasing, the amounts of growing degree-day without exception increases in review periods and under the four Base temperature. Under studied scenarios, the Bases temperature of 0° centigrade had the most and 15° centigrade had the least impressibility from climate changes, so that the most increasing in calculated degree-day measures under 0° and 15° centigrade bases in the first period to the basic scenario (1985-2009) respectively was simulated as 207/4 and 120/6 degree-day under A2 scenario and for the second period to the 752/5 and 463/5 degree-day under A1B scenario.